The Energy Landscape Perspective: Encoding Structure and Function for Biomolecules - Röder, Konstantin; Wales, David J. (Frontiers in Molecular Biosciences, 2022)
The energy landscape perspective is outlined with particular reference to biomolecules that perform multiple functions. We associate these multifunctional molecules with multifunnel energy landscapes, illustrated by some selected examples, where understanding the organisation of the landscape has provided new insight into function. Conformational selection and induced fit may provide alternative routes to realisation of multifunctionality, exploiting the possibility of environmental control and distinct binding modes.